Variable origin of vertebral artery : A Cadaveric and Multidetector computed tomographic study on Indian population - Vanita Sharma; Anju Pratap; Sushma Makhaik; Kunal Chawla; Neeraj Kumar; Ankur Gupta (Wolters Kluwer Medknow Publications, 2018)
Background: The knowledge of normal and variant anatomy of vertebral artery is important for the interpretation of vascular radiology and in performing safe vascular procedures like repair of aneurysms, excision of craniocervical junction masses & vertebral endarterectomy. Aim: To find out incidence of left vertebral artery of aortic origin in North Indian population. Materials & Method: During routine dissection of thoracic region, an anatomical variation of origin of left vertebral artery of aortic origin was observed in adult male cadaver. To find out incidence of left vertebral artery of aortic origin in North Indian population, Radiological study was done on 100 patients [34 female + 66 males] who were advised computed tomography of neck & thorax for various indication. Diameter of left vertebral artery at origin from arch of aorta and where it entered foramen transversarium was measured. Length of VI segment i.e. from its origin to where it entered foramen transversarium was also measured. Result: Out of 100 patients, left vertebral artery of aortic origin was observed in 4 patients. Conclusion: Aortic origin of vertebral artery is of diagnostic importance prior to surgery in neck & chest regions. Cadaveric metrological studies are also helpful to design aortic stent